Rewriting cellular fate: epigenetic interventions in obesity and cellular programming - Rui-lin Li; Sheng Kang (BMC, 2024)
Abstract External constraints, such as development, disease, and environment, can induce changes in epigenomic patterns that may profoundly impact the health trajectory of fetuses and neonates into adulthood, influencing conditions like obesity. Epigenetic modifications encompass processes including DNA methylation, covalent histone modifications, and RNA-mediated regulation. Beyond forward cellular differentiation (cell programming), terminally differentiated cells are reverted to a pluripotent or even totipotent state, that is, cellular reprogramming. Epigenetic modulators facilitate or erase histone and DNA modifications both in vivo and in vitro during programming and reprogramming. Noticeably, obesity is a complex metabolic disorder driven by both genetic and environmental factors. Increasing evidence suggests that epigenetic modifications play a critical role in the regulation of gene expression involved in adipogenesis, energy homeostasis, and metabolic pathways. Hence, we discuss the mechanisms by which epigenetic interventions influence obesity, focusing on DNA methylation, histone modifications, and non-coding RNAs. We also analyze the methodologies that have been pivotal in uncovering these epigenetic regulations, i.e., Large-scale screening has been instrumental in identifying genes and pathways susceptible to epigenetic control, particularly in the context of adipogenesis and metabolic homeostasis; Single-cell RNA sequencing (scRNA-seq) provides a high-resolution view of gene expression patterns at the individual cell level, revealing the heterogeneity and dynamics of epigenetic regulation during cellular differentiation and reprogramming; Chromatin immunoprecipitation (ChIP) assays, focused on candidate genes, have been crucial for characterizing histone modifications and transcription factor binding at specific genomic loci, thereby elucidating the epigenetic mechanisms that govern cellular programming; Somatic cell nuclear transfer (SCNT) and cell fusion techniques have been employed to study the epigenetic reprogramming accompanying cloning and the generation of hybrid cells with pluripotent characteristics, etc. These approaches have been instrumental in identifying specific epigenetic marks and pathways implicated in obesity, providing a foundation for developing targeted therapeutic interventions. Understanding the dynamic interplay between epigenetic regulation and cellular programming is crucial for advancing mechanism and clinical management of obesity.